PENGARUH SKEPTISISME PROFESIONAL, META PROGRAM, DAN MORAL REASONING AUDITOR TERHADAP KUALITAS AUDIT PENGAWASAN KEUANGAN DAERAH PADA INSPEKTORAT KABUPATEN BANYUMAS - Anna Widya Darajati; Eko Suyono (Jurnal Riset Keuangan dan Akuntansi, 2021)
ABSTRACTThis study is a survey on auditors of the Inspectorate of Banyumas Regency that aims to determine and analyze the effect of professional skepticism, meta program, and moral reasoning auditors on the audit quality of regional financial supervision at the Inspectorate of Banyumas Regency. Respondents included the auditors of the Banyumas Regency Inspectorate consisting of functional auditors, Supervisory Officers for Regional Government Affairs, and other structural officials. Based on the results of data analysis using multiple linear regression, it shows that: (1) Auditor's professional skepticism has a positive and significant effect on audit quality, (2) Auditor's meta program has a positive and significant effect on audit quality, (3) Auditor's moral reasoning has no significant effect. on audit quality. Therefore, the implication of this study is that increasing critical attitude, procedural thinking style, and high commitment could be improved through regular audit training for the inspectorate apparatus in Banyumas. Keywords: Audit Quality, Professional Skepticism, Meta Program, Moral Reasoning